2020
DOI: 10.21608/adjg.2020.14158.1181
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Accuracy and Microleakage of Machinable Laminate Veneers

Abstract: Purpose:The current study aimed to evaluate the marginal accuracy and microleakage of machinable laminate veneers. Materials and Methods: Twentyfour human maxillary central incisor teeth were collected and prepared (butt-joint preparation) to receive laminate veneers. They were divided into three groups (n=8) according to material of construction: Group I: IPS-Emax CAD, Group II: Vita Suprinity, Group III: Celtra-Duo. The veneers were milled from the blocks in a CEREC 3 Machine. All veneers were cemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…33 The first null hypothesis was rejected as there was significant difference regarding the marginal adaptation of occlusal veneers made of different materials. Celtra Duo showed lower marginal gap compared to IPS e.max CAD occlusal veneers, this result came in accordance with Ahmed, et al, (2020) (34) and Basheer, et al, (2017) 35 . Celtra Duo microstructure as claimed by the manufacturer to present high edge stability providing acceptable margins.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…33 The first null hypothesis was rejected as there was significant difference regarding the marginal adaptation of occlusal veneers made of different materials. Celtra Duo showed lower marginal gap compared to IPS e.max CAD occlusal veneers, this result came in accordance with Ahmed, et al, (2020) (34) and Basheer, et al, (2017) 35 . Celtra Duo microstructure as claimed by the manufacturer to present high edge stability providing acceptable margins.…”
Section: Discussionsupporting
confidence: 85%
“…Another reason may be attributed to difficulties during restoration designing regarding scanning, digitization, and the milling process, milling burs size and the condition of the material during the milling procedure. (34) The difference in marginal gap between the two materials could be attributed also to the fact that the Celtra Duo was milled in a fully crystallized form and IPS e.max CAD was milled in a partially crystallized form. Therefore, IPS e.max CAD is expected to have had more shrinkage as compared to Celtra Duo after heat treatment due to densification of the ceramic material increasing marginal gap in the IPS e.max CAD.…”
Section: Discussionmentioning
confidence: 99%
“…(67) Group CD table-tops fabricated from Celtra DUO, showed better marginal and internal adaptation than table-tops fabricated from e.max CAD in group ED. This result came in agreement with Ahmed et al, (74) Basheer et al, (75) , and Abuhajar et al, (42) , the microstructure of Celtra Duo, as manufacturer claims, presented increased edge stability, so offering satisfactory margins. (76) While inferior marginal and internal adaptation of e. max CAD resulted from dimension changes that happened during the crystallization firing stage as CD restorations were milled in a fully crystallized state, while ED restorations were milled in partially crystallized form.…”
Section: Discussionsupporting
confidence: 90%
“…Due to their unique synergistic properties with UV-activated (light) chemical cements, dual-cure cements are perfect for treating deep cavities like those seen in root canals. The goal of dual-cure cements can only be satisfactorily achieved if the crucial preparation of the tooth root employing an adhesive method [16] is carried out. Initially applied in three processes, several adhesive solutions were eventually applied in two steps, and most recently, one self-etch step [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of dual-cure cements can only be satisfactorily achieved if the crucial preparation of the tooth root employing an adhesive method [16] is carried out. Initially applied in three processes, several adhesive solutions were eventually applied in two steps, and most recently, one self-etch step [16,17]. However, research has shown that this property of the acid resinous monomers found in the surface layer of the two-step and self-etching systems can weaken the adhesive binding to root dentin, causing marginal leakage in the future that ultimately results in a poor prognosis for the restoration [18,19].…”
Section: Introductionmentioning
confidence: 99%